2001
DOI: 10.1093/hmg/10.5.477
|View full text |Cite
|
Sign up to set email alerts
|

WFS1 (Wolfram syndrome 1) gene product: predominant subcellular localization to endoplasmic reticulum in cultured cells and neuronal expression in rat brain

Abstract: Wolfram (DIDMOAD) syndrome is an autosomal recessive neurodegenerative disorder accompanied by insulin-dependent diabetes mellitus and progressive optic atrophy. Recent positional cloning led to identification of the WFS1 (Wolfram syndrome 1) gene, a member of a novel gene family of unknown function. In this study, we generated a specific antibody against the C-terminus of the WFS1 protein and investigated its subcellular localization in cultured cells. We also studied its distribution in the rat brain. Bioche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
246
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 302 publications
(257 citation statements)
references
References 25 publications
8
246
0
3
Order By: Relevance
“…Beta cells are selectively lost from the pancreatic islets and this loss is genetically programmed [10]. Our group and others previously identified the Wolfram syndrome gene, designating it WFS1 [11] or wolframin [12] and showing that it is localised primarily in the ER [13,14]. Homozygous Wfs1 knockout mice developed glucose intolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Beta cells are selectively lost from the pancreatic islets and this loss is genetically programmed [10]. Our group and others previously identified the Wolfram syndrome gene, designating it WFS1 [11] or wolframin [12] and showing that it is localised primarily in the ER [13,14]. Homozygous Wfs1 knockout mice developed glucose intolerance.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 This gene is located on chromosome 4p16.3 and encodes Wolframin, a transmembrane protein that maintains calcium homeostasis of the endoplasmic reticulum (ER). [8][9][10][11] Other roles, such as regulation of ER stress and protein biosynthesis, modification/ folding, have also been suggested for Wolframin. [12][13][14][15] Wolframin is an 890 amino acid oligomeric protein with a molecular mass of 100 kDa.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that Wolframin is an endoplasmic reticulum (ER) membrane-embedded protein. 7 ER localization suggests that Wolframin has physiological function in membrane trafficking, secretion, processing and/or regulation of ER calcium homeostasis. Disturbances or overloading of these functions induce ER stress responses, including apoptosis.…”
Section: Discussionmentioning
confidence: 99%